2021
DOI: 10.3390/ijerph182111457
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Algic Syndrome Treatment in Long COVID—Cases Reports

Abstract: Though pain is a frequent symptom of long COVID-19, little attention has been paid to vertebral algic syndrome. Therefore, we present the cases reports of two precisely selected physically active patients where vertebral algic syndrome and radiculopathy dramatically worsened in acute SARS-CoV-2 infections. The vertebral pain with radicular irritation was resistant to conservative treatment in chronic post-COVID syndrome. The neurological difficulties corresponded to the radiologic imaging presented on MRI scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 38 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…The symptoms of long COVID were varied. First, there were some physical symptoms: fatigue [ 9 , 12 , 35 ], dyspnea [ 35 , 36 ], cough [ 35 , 36 ], loss of taste or smell [ 12 ], loss hair [ 9 ], fever [ 35 , 37 ], sleep disorder [ 38 ], joint pain [ 39 , 40 ], headache [ 41 ], spinal pain [ 42 ], muscle pain [ 39 , 43 ], diarrhea [ 44 ], and organ (heart, lungs, kidneys, liver, pancreas, and spleen) damage [ 45 ]. Second, there were some mental symptoms: insomnia, delirium, fear, and depression [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms of long COVID were varied. First, there were some physical symptoms: fatigue [ 9 , 12 , 35 ], dyspnea [ 35 , 36 ], cough [ 35 , 36 ], loss of taste or smell [ 12 ], loss hair [ 9 ], fever [ 35 , 37 ], sleep disorder [ 38 ], joint pain [ 39 , 40 ], headache [ 41 ], spinal pain [ 42 ], muscle pain [ 39 , 43 ], diarrhea [ 44 ], and organ (heart, lungs, kidneys, liver, pancreas, and spleen) damage [ 45 ]. Second, there were some mental symptoms: insomnia, delirium, fear, and depression [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Instead, personalized treatment was recommended for each patient [ 30 , 49 , 50 ]. For specific symptoms, there were the following studies: (1) Robbins Tim et al used hyperbaric oxygen therapy to treat chronic fatigue syndrome, which significantly improved fatigue [ 51 ]; Vollbracht C and Kraft K believed that injections of Vitamin C can help relieve symptoms of fatigue [ 52 ]; and (2) Dzubera A et al used spinal surgery with radicular decompression to treat spinal pain in patients [ 42 ]. (3) Maria Ines Mitrani et al found that amniotic fluid-derived extracellular vesicle biologic could be used to treat respiratory disorders [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The brain [ 7 ], spinal cord [ 8 , 9 , 10 , 11 ], and peripheral nerves [ 7 , 12 ] can be affected in acute and chronic COVID-19 [ 4 , 5 ]. The SARS-CoV-2 associated back difficulties and radicular pain are of sparse occurrence in literature [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is sparse information of neural root impairment in COVID-19. Only anecdotal clinical case reports of back pain in acute [ 13 ] and long COVID-19 [ 14 ] were presented. Back pain with radicular or pseudoradicular syndrome was the first complaint in acute SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation